Determinants of Islamic Digital Banking Adoption: Extending UTAUT3 with Islamic Lifestyle Moderation in Indonesia - Sugianto; Muhammad Lathief Ilhamy Nasution; M. Fauzan; Muhammad Alwan Atha (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid digitalization of financial services has transformed global banking, yet the adoption of Islamic digital banking remains limited in emerging economies. The study examines the effects of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and personal innovativeness on customers’ behavioral intention to adopt Islamic digital banking. This study investigates the determinants of Islamic digital banking adoption in Indonesia by extending the Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) with Islamic lifestyle as a moderating factor. The research uses quantitative and survey data from 147 active Islamic banking customers across Sumatra and employs Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all UTAUT3 constructs significantly and positively influence adoption intention, indicating that both rational–instrumental and behavioral–psychological factors shape digital banking decisions. Furthermore, Islamic lifestyle significantly moderates these relationships, enhancing the impact of technological and behavioral determinants when services align with Islamic values. The study contributes theoretically by integrating UTAUT3 with Islamic Lifestyle Theory and offers practical guidance for Islamic banks and policymakers to design Sharia-compliant digital strategies that combine efficiency with ethical and religious value alignment, highlighting the importance of value congruence in sustainable adoption.